Karakteristik Kimia Tanah pada Beberapa Penggunaan Lahan di Desa Lumut Kecamatan Toba Kabupaten Sanggau - Ningsih, Ratih Citra; Nusantara, Rossie Wiedya; Manurung, Rinto (Pedontropika: Jurnal Ilmu Tanah dan Sumber Daya Lahan, 2024)
There has been no research on the analysis of soil chemical properties at the location, so this research was conducted to see how significant the differences in soil chemical properties are that occur in several land uses and slope classes, including oil palm plantations, rubber plantations and shrubs in Lumut Village, Toba District, Sanggau Regency. carried out within 6 months. Using a purposive random sampling method with an area of 12.5 ha per point, observation points were determined based on land use, slope class and soil type. The number of samples taken was 38 samples, the research parameters consisted of soil pH, C-organic, N-total, P-available, K-total, Ca-dd, Mg-dd, Na-dd, K-dd, KTK, KB and Saturation Al. The results of the research show that in the land use of oil palm plantations, rubber plantations and shrubs the pH parameter is classified as sour in the range of 4.84-5.36, the C-Organic criteria are medium to high at a value of 2.32-3.08%, N-Total criteria are moderate to very high at a value of 0.30-0.33%, P-available criteria are very low at a value of 4.71-8.52 mg/100 g, K-total criteria are very low at a value of 4.30 -6.42 mg/100 g, Ca-dd very low criteria at a value of 0.52-0.77 me/100 g, Mg-dd very low criteria at a value of 0.18-0.28 me/100 g, Na -dd low criteria at a value of 0.23-0.30 me/100 g, K-dd very low criteria at a value of 0.07-0.08 me/100 g, CEC medium to high criteria at a value of 20.45-32 .61 cmol(+)kg-1, and KB is classified as very low at a value of 4.18-11.47%, Al saturation criteria is very low at a value of 1.32-3.10 cmol(+)kg-1. The results of the research require further study of the characteristics of Ultisol soil at different depths and a study of soil fertility is needed so that it can be used as a reference for fertilization so that it is more targeted and produces the desired harvest.